ANALISIS USAHA PERLEBAHAN TERHADAP PENDAPATAN KELUARGA TANI DESA SIPATUHU 1 BANDING AGUNG KABUPATEN OKU SELATAN - Iman Sulaiman (Jurnal Bakti Agribisnis, 2015)
The purpose of this research were to : (1) To find out how much income and contributions received from businesses in the village beekeeping Sipatuhu, (2) To determine the feasibility of beekeeping in the village Sipatuhu. This study was conducted at the District Court of Appeal Sipatuhu 1 South OKU. The determination of this research is done intentionally (purposive), arguing there is only one beekeeping businesses in the village Sipatuhu 1 District of South OKU District Court of Appeal. Research has been conducted in May and June 2013. The study found that the average cost of production enterprises Apis mellifera beekeeping for one year is Rp 2,144,757, Rp reception 8.53125 million / year and an income of Rp 6,386,493 / year , Value beekeeping business contribution to the family income Apis mellifera is small with a value of 4.8%. Rated feasibility of Apis mellifera beekeeping Rp 47,224,232 NPV, IRR 130.81% and Net B / C of 6.94.